The Determination of Protonation Constants of Peptidomimetic Cyclophanes in Binary Methanol-Water Mixtures - Piotr Seliger; Danuta Tomczyk; Grzegorz Andrijewski; Ewa Tomal (Journal of Analytical Methods in Chemistry)
The protonation constants of new group of peptidomimetic cyclophanes with valine or phenylalanine moieties incorporated into the macrocyclic skeleton as well as their linear analogues were determined by potentiometric measurements in solutions of methanol-water mixtures at 25°C and constant ionic strength. The influence of cavity size, location of protonation sites, and attached substituents of the macrocyclic ligands on the protonation constants were discussed on the basis of potentiometric measurement as well as H1-NMR results.